Effect of sow’s parity and semen storage time on reproductive performance of pig after artificial insemination with liquid boar semen - SINGH, MAHAK; MOLLIER, R TALIMOA; PONENER, NUNGSHITULA; CHAUDHARY, J K; KUMAR, RAKESH; RAJKHOWA, D J; MISHRA, V K (The Indian Journal of Animal Sciences, 2022)
Artificial insemination with liquid stored boar semen has considerably improved the pig genetic throughout the world. The present study analyzed the effect of sow's parity and semen storage time on reproductive performance of pig after artificial insemination with liquid boar semen. A total of 218 Gunghroo × Hampshire female pigs including gilts (42) and sows (176) were inseminated with liquid stored semen. Reproductive performance parameters, including farrowing rate, gestation length, weaning to estrous interval, total piglets born, total live piglets born, stillborn piglets, mummified piglets and litter size at weaning were analyzed between different parity and also between different semen storage duration (24 h, 24 to 48 h and 48 to 72 h). There was no effect of parity on farrowing rate. Gestation length was significantly higher in third, fourth and fifth parity as compared to first and second parity. Weaning to estrus interval was significantly higher in first parity. Total piglets born and total live piglets born were significantly higher in third, fourth and fifth parity as compared to first and second parity. There was no effect of parity on stillborn and mummified piglets. Litter size at weaning was significantly higher in third to fifth parity as compared to first and second parity. There was no effect of semen storage duration on farrowing rate, gestation length and weaning to estrus interval. Total piglets born, total live piglets born and litter size at weaning were significantly higher in first group as compared to second and third group. There was no effect of semen storage time on stillborn and mummified piglets. In conclusion, artificial insemination in pig could be successfully used with promising reproductive performance under sub-tropical climatic condition. However, a decrease in litter size was observed when insemination was done with semen stored for more than 24 h.